IMPLEMENTASI PEMBELAJARAN BLENDED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR - Afrida Hanum; Nena Puspita Sari; Siti Rahmatina (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
This study aimed to determine the effect of the implementation of blended learning to improve the learning outcomes of primary school students. The method used is quasi-experimental method with quantitative approach. The research design used was